Sinbiotik Ekstrak Ubi Ungu dan Probiotik Lokal pada Yogurt: Kesehatan Pencernaan, Hematologi, dan Sistem Imun - Agustina Intan Niken Tari; Catur Budi Handayani; Sri Hartati (agriTECH, 2020)
The bacteria presence in the gastrointestinal tract is one of the important factors determining the support for body health among others. Therefore, it is essential to maintain a population balance, possibly achieved by consuming local probiotic-based sinbiotic yoghurt. The purpose of this study, therefore, was to evaluate the effectiveness of purple sweet potato extracts and local probiotics supplemented in yogurt by a healthy profile. Furthermore, the Health parameters evaluated include gastrointestinal (faecal water), hematology (number of erythosit, leukocyte, hemoglobin and hemtocrit) and immune system (antibody titer) in Spraque dawley albino mice. This study was performed using a Completely Randomized Design on 30 rats divided into 6 groups.  Therefore, those in group K- were administered distilled water from day 1st -21st, YTP =  yogurt without probiotics from day 1st -21st, YDP = probiotic yogurt from day  1st- 21st,  YTP+E = yogurt without probiotic from day 1st- 21st, interspersed EPEC on day 8th – 14th, YDP+E = yogurt from day1st- 21st, interspersed EPEC on day  8th-14th, K + = water from day 1st- 21persed EPEC on day 8th – 14th, YDP+E = probiotic yogurt from day1st- 21st, then fed EPEC on day 8th- 14th. The results showed the effectiveness of probiotic yogurt treatment with purple sweet potato extract supplementation in healthy gastrointestinal (faecal water), hematology (number of erythrocyte, leukocyte, hemoglobin and hematocrit) and immune system (titre antibodies). This phenomenon results from infection by EPEC (Enteropathogenic Eshericchia coli), which is responsible for diarrhea. Furthermore, the YDP treatment possessed a water content characterized by 48.42% feces, while the number of erythrocytes, leucocytes, haemoglobin and hematocrit were 8,58x106/μl, 14,15 x106/μl, 13.98 g/dL and 47,67 mL%, respectively. Moreover, 6,42 log of antibody titers was also determined.